Depression coping strategies in Mexican adolescents - González Escobar, Sergio (Consorcio de Universidades Mexicanas A.C., 2012)
In regard to depression, adolescents are among the highest at-risk members of the population and research findings reveal that the onset age of this disease is descending. Consequently those who suffer from depression in this age period usually wait around two years before asking for attention. In addition, Mexican research has neglected the study of the coping strategies that adolescents use when they are depressed. Such a study is the aim of the here reported investigation. A non-probabilistic sample of 400 adolescents attending elementary and high schools was investigated. Half of them were boys and the rest were girls. The Natural Semantic Network was used as instrument, which was administered at students’ classrooms. Results showed that students consistently define their strategies across educational level; yet such a consistency is not present when boys and girls are grouped by total samples. The use of the Natural Semantic Network was appropriate for the intended goal of the study. An important finding is that the coping strategies that adolescents use are not helpful in achieving healthy states and in preventing the occurrence of depression, working only as mere palliatives.